Effect of Wedang Ginger Giving on Emesis Gravidarum in Pregnant Women in the Trimester I - Maya Saroisong, Yantie; Nulhakim, Lukman; Raihanah, Siti (Jurnal KESANS : Kesehatan dan Sains, 2024)
Introduction: In pregnancy, the mother experiences changes in terms of physical and psychological. One of the most common in the first trimester is emesis gravidarum. Implementation of nausea and vomiting by giving ginger wedang. Objective: The purpose of this study is to determine the effect of ginger wedang on emesis during pregnancy. Method: Using a quasy esperiment without control research design. The population in this study is 30 pregnant women in the first trimester. The instrument used in the study used an observation sheet to monitor emesis scores. The statistical analysis used is the Wilcoxon test. Results and Discussion: The administration of ginger wedang intervention reduces nausea and vomiting in emesis gravidarum by relaxing and weakening the muscles of the gastrointestinal tract so that nausea and vomiting have antiemetics, namely essential oils that can block serotonin which causes nausea and vomiting, in addition to the fragrant aroma of ginger if inhaled can make the feeling relaxed so that nausea and vomiting do not occur. Conclusion: the results of the study from 30 respondents were 25 respondents who experienced a decrease in emesis gravidarum and 5 respondents who did not experience a decrease in emesis gravidarum due to lack of cooperation in following the instructions given, namely irregularly drinking ginger wedang and continuing to consume fatty foods (offal, fried foods, chicken with coconut milk sauce and sharp smell).